2022
DOI: 10.1037/pspi0000374
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contact effects: Individuals’ positive and negative contact history influences intergroup contact effects in a behavioral game.

Abstract: Positive contact between members of different groups reduces prejudice and increases cooperation, findings known as intergroup contact effects. Yet in real-world settings not only positive, but also negative intergroup contact occurs, which have opposing effects. To date little is known about whether and how an individual's valenced history of intergroup contact influences contact effects and how this dynamic change happens during specific instances of intergroup contact. A pilot study examined the psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…For several reasons, our findings do not imply a complete absence of within-person effects in the intergroup contact literature, nor a fundamental conflict with the contact hypothesis. Not least, there is an abundance of (quasi-)experimental studies attesting to the intra-individual effect of contact on attitudes when contact is externally induced (Guffler & Wagner, 2017; Reimer et al, 2022; Schäfer et al, 2022; van Zalk et al, 2021; Wölfer et al, 2016). In contrast, the present data sets did not show substantial changes in contact over time, and the within-person and between-person variance distribution was either about equal (Study 1) or favored the between-person part (Study 2), which might make it implausible to expect significant within-person effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For several reasons, our findings do not imply a complete absence of within-person effects in the intergroup contact literature, nor a fundamental conflict with the contact hypothesis. Not least, there is an abundance of (quasi-)experimental studies attesting to the intra-individual effect of contact on attitudes when contact is externally induced (Guffler & Wagner, 2017; Reimer et al, 2022; Schäfer et al, 2022; van Zalk et al, 2021; Wölfer et al, 2016). In contrast, the present data sets did not show substantial changes in contact over time, and the within-person and between-person variance distribution was either about equal (Study 1) or favored the between-person part (Study 2), which might make it implausible to expect significant within-person effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although separating within-person and between-person effects is critical to understanding the association between contact and attitudes, few studies have employed adequate analytical techniques to investigate these effects (Barlow et al, 2019; Bohrer et al, 2019; Boin et al, 2020; Schäfer et al, 2022), and none has compared and discussed differences across models that can and cannot separate these analysis levels. One study used methodology comparable to the present study and found few within-person processes, but strong between-person associations between contact and attitudes (Bohrer et al, 2019).…”
Section: Within-person and Between-person Effects Of Contact On Attit...mentioning
confidence: 99%
“…Only recently has the importance of valence of contact become a topic of study after a long period in which the field was dominated by positive intergroup contact research (Paolini et al, 2010). Positive contact is experienced more frequently than negative contact in a number of different settings with varying degrees of intergroup friction (Graf et al, 2014; Schӓfer, Simsek, et al, 2021). While it is no surprise that positive contact is found to relate to prejudice reductions and negative contact to prejudice exacerbation, emerging evidence has now shown that negative intergroup contact might enhance prejudice more than positive intergroup contact decreases it (Barlow et al, 2012; Graf & Paolini, 2017).…”
Section: Valence Of Contactmentioning
confidence: 99%
“…While it is no surprise that positive contact is found to relate to prejudice reductions and negative contact to prejudice exacerbation, emerging evidence has now shown that negative intergroup contact might enhance prejudice more than positive intergroup contact decreases it (Barlow et al, 2012; Graf & Paolini, 2017). Still, findings regarding a stronger impact of negative contact are rather mixed (for overviews, see Paolini &McIntyre, 2019; Schӓfer, Kauff, et al, 2021) and several factors may influence the interplay between positive and negative contact, including histories of contact (Kotzur & Wagner, 2021; Paolini et al, 2014), valenced expectations (Schӓfer, Simsek et al, 2021), level of intimacy (Fuochi et al, 2020) and intensity of the contact experience (Schӓfer, Kros, et al, 2021). Drawing on this research, in Study 1 we combine volition and valence of contact in our design to better understand the interaction of these modes of contact and their downstream consequences for intergroup relations.…”
Section: Valence Of Contactmentioning
confidence: 99%
“…Indeed, empirical evidence indicates that negative portrayals and limited positive portrayals of minority groups in the media foster prejudicial perceptions of minority groups, propagating negative stereotypes (Mastro, 2009). Although mediated-contact effects can be positive or negative depending on the depiction of the outgroup, the “light” and “dark” sides are rarely studied together or even under the same theoretical umbrella (Harwood, 2010; Schäfer et al, 2021). Our model is designed to account for positive and negative contact experiences by providing hypothesized relationships between explanatory and intervening variables and outgroup prejudice.…”
Section: Theoretical and Practical Implications Of The Imic Modelmentioning
confidence: 99%